If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = x + (-2) -15 = x + -2 Reorder the terms: -15 = -2 + x Solving -15 = -2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -15 + -1x = -2 + x + -1x Combine like terms: x + -1x = 0 -15 + -1x = -2 + 0 -15 + -1x = -2 Add '15' to each side of the equation. -15 + 15 + -1x = -2 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = -2 + 15 -1x = -2 + 15 Combine like terms: -2 + 15 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13
| (5x+15)(10x-8)= | | https://college.measuredsuccess.com/mscollege/itemImages/1010010011035000001020008q.gif | | 13=x-(-14) | | 6h+h=30 | | 4x+34=114 | | 21a^5-7a^6= | | p+0.06=360.40 | | w-7/2w-14 | | f(x)=2.3x+7 | | -8=-4+v | | 16a^4-8a^6= | | -4x+3=6x-63 | | 4/9x^2-16=0 | | 3(0.3m+6)+m=75 | | 13=-7b-6b | | x^7-x^5= | | -x=-a/13 | | (1/2)(5x)(4x-1)= | | -n+7n=18 | | x^2+29x+79=0 | | 9x-29/10 | | 4(m-s)=24 | | 2(4z-5-3)=166-48 | | x+41=-90 | | 2/3x5/1 | | Y-4=-1/4(x-3) | | x+41= | | (-6)+(6)= | | 8x=-120/18 | | 40+3a=-5 | | 3(3x-6)=-(x-2) | | -2/3u=-4 |